Apyrase decreases phage induction and Shiga toxin release from E. coli O157:H7 and has a protective effect during infection - Ida Arvidsson; Ashmita Tontanahal; Karl Johansson; Ann-Charlotte Kristoffersson; Sára Kellnerová; Michael Berger; Ulrich Dobrindt; Diana Karpman (Gut Microbes)
Shiga toxin (Stx)-producing enterohemorrhagic Escherichia coli (EHEC) cause gastrointestinal infection and, in severe cases, hemolytic uremic syndrome which may lead to death. There is, to-date, no therapy for this infection. Stx induces ATP release from host cells and ATP signaling mediates its cytotoxic effects. Apyrase cleaves and neutralizes ATP and its effect on Stx and EHEC infection was therefore investigated. Apyrase decreased bacterial RecA and dose-dependently decreased toxin release from E. coli O157:H7 in vitro, demonstrated by reduced phage DNA and protein levels. The effect was investigated in a mouse model of E. coli O157:H7 infection. BALB/c mice infected with Stx2-producing E. coli O157:H7 were treated with apyrase intraperitoneally, on days 0 and 2 post-infection, and monitored for 11 days. Apyrase-treated mice developed disease two days later than untreated mice. Untreated infected mice lost significantly more weight than those treated with apyrase. Apyrase-treated mice exhibited less colonic goblet cell depletion and apoptotic cells, as well as lower fecal ATP and Stx2, compared to untreated mice. Apyrase also decreased platelet aggregation induced by co-incubation of human platelet-rich-plasma with Stx2 and E. coli O157 lipopolysaccharide in the presence of collagen. Thus, apyrase had multiple protective effects, reducing RecA levels, stx2 and toxin release from EHEC, reducing fecal Stx2 and protecting mouse intestinal cells, as well as decreasing platelet activation, and could thereby delay the development of disease.